Excitonic properties of deep-blue emitting fragmented CsCl:Eu2+ nanocrystals - Kim, Panju; Kim, Minjin; Kim, Ga-Eun; Lee, Eunyoung; Moon, Byung Joon; Il Park, Yong; Lee, Sang Hyun (Elsevier, 2024)
In this work, polycrystalline CsCl:Eu2+ 2 + nanocrystals were grown by the hot injection method. The CsCl:Eu2+ 2 + nanocrystals were fragmented into particles of a few nanometers by dispersion in organic solvents, and they exhibited strong deep-blue emission under ultraviolet light. Excitonic emission at room temperature was observed near 410 nm, with a full width at half-maximum of 37.8 nm and a photoluminescence quantum yield of 4.1%. Additionally, the average exciton lifetime was determined to be 6.45 ns. In the temperature range of 10 K to 300 K, the excitonic emission intensity gradually decreased while the energy of the peak position slightly increased, corresponding to an increase in the temperature. From the result, the exciton binding energy and average longitudinal phonon energy were calculated to be about 29 and 13 meV, respectively, comparable to the energy calculations of similar Cs-series perovskites. Thermal expansion and electron-phonon interaction also increased steadily with the temperature, and these two phenomena gave rise to a monotonic blue-shift.